Analysis of the Positive and Negative Impacts of Using Tiktok For Generation Z During Pandemic - Ni Putu Utari Oktarini; Ni Putu Kristina Dewi; Made Riski Aditya Kencana Putra; Jen Herens Arnas Ataupah; Ni Luh De Dian Oktarini (Journal of Digital Law and Policy, 2022)
Social media is broadly commonplace in today's daily life, even some people can't live without it. One of the most downloaded apps this year is Tiktok. Tiktok is the most used application since the pandemic until now. No wonder the impact on many sectors in the world. In this article, the author will analyze the positive and negative impacts of using TikTok for Generation Z during a pandemic. The method used in writing this article is to use a literature study. The writing of this article is based on references from various articles about the use of tiktok, tiktok journals and also Google. The search is limited to generation Z keywords and the use of Tiktok. The results of the study found that TikTok can be used to encourage the creativity of Generation Z to create a work, as a place for self-expression, as a place for education, and entertainment. However, the TikTok application is widely misused by children, adults and parents. As for some of the negative impacts of using the application, namely syndromic, sexual harassment, tutorials in learning and lack of association with people around. In conclusion, the use of Tiktok social media is indeed beneficial, but there are also positive and negative sides. Therefore, more research and further models are needed for its application in its activities.